Expressive Thesis Writing: Strategi Reflektif untuk Mengatasi Burnout Akademik Mahasiswa Matematika Tingkat Akhir - Nenotaek, Bakher; Sabat, Alse Ona (Mandalika Mathematics and Educations Journal, 2025)
Academic burnout is a significant issue among final-year students, especially in mathematics study programs that are known to have a high level of difficulty. This study examines the effectiveness of expressive thesis writing as a reflective strategy for overcoming academic burnout. Using a mixed quantitative and qualitative approach, the study involved 36 mathematics students preparing their final project. The intervention was carried out through expressive writing for five consecutive days. The results of the analysis showed that the burnout of final-level students was in the high category with a score of 67% or as many as 24 respondents experienced burnout and the medium category with a score of 33% or as many as 12 respondents. Thematic analysis of respondents' writings revealed key themes such as existential anxiety, role conflicts, and self-acceptance processes. This study suggests expressive writing as an applicable psychological approach in academic guidance. Keywords: Expressive writing; Academic burnout; Final project